MC3R gene polymorphisms are associated with early childhood adiposity gain and infant appetite in an Asian population*. Issue 6 (11th December 2015) - Aris, I. M.; Tint, M. T.; Teh, A. L.; Holbrook, J. D.; Quah, P. L.; Chong, M. F.‐F.; Lin, X.; Soh, S. E.; Saw, S.‐M.; Kwek, K.; Godfrey, K. M.; Gluckman, P. D.; et al.
Summary: Background: Polymorphic variants within human melanocortin‐3 receptor gene ( MC3R ) gene have been associated with obesity. However, its influence on infancy and early childhood adiposity has not been reported before. Objectives: We assessed associations between genotype at polymorphic sites within MC3R with early childhood adiposity and interaction with early childhood appetitive traits. Methods: We studied 1090 singletons in an Asian mother–offspring cohort genotyped for MC3R and in a subgroup ( n  = 422) who had completed Child Eating Behaviour Questionnaires (CEBQ) at 12 months. Children were followed from birth to 48 months, and up to 10 measurements of body mass index and five measures of triceps and subscapular skin‐folds were obtained. Results: Independent of potential confounders, each additional MC3R minor allele copy was associated with greater body mass index standard deviation score [B{95% confidence interval}: 0.004 units/month {0.001, 0.007}; p  = 0.007], triceps [0.009 mm/month {0.001, 0.02}; p  = 0.021] and subscapular skin‐fold [0.008 mm/month {0.002, 0.01}; p  = 0.011] gain velocity in the first 48 months. Each additional MC3R minor allele copy was also associated with increased odds of overweight [odds ratio {95% confidence interval}: 1.48{1.17–1.88}] and obesity [1.58{1.10–2.28}] in the first 48 months. Every additional copy of MC3R minor allele was positively associated with 'slowness‐in‐eating' appetitive trait [0.24{0.06, 0.39}, p  = 0.006]; however, the relationship between 'slowness‐in‐eating' with adiposity gain was not statistically significant. Conclusions: Our findings support the role of MC3R genetic variants in adiposity gain during early childhood.